1990
DOI: 10.1007/bf00009275
|View full text |Cite
|
Sign up to set email alerts
|

Starch synthesis in potato (Solanum tuberosum) tubers: Activity of selected enzymes in dependence of potassium content in storage tissue

Abstract: Starch synthesis in potato tubers grown at varied K nutrition (0.1 (K1), 0.25 (K2) and 1.0 mmol K L-I nutrient solution (K3) was investigated with particular regard to the activity of selected enzymes (sucrose synthase, UDP-D-glucose pyrophosphatase, starch phosphorylase, amylases) in dependence on tuber K content. Allocation of K to the tubers was nearly the same in all treatments. The activity of enzymes related to tuber K content did not differ significantly. Starch and K content of tubers increased with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Earlier Flowers and Dalmond (1992) have shown that protein synthesis in halophytes and glycophytes had different requirements for essential nutrients such as K and Mg, with the later impacting the polysome translocating system. Another evidence comes from the observation that starch synthetase, an enzyme that tightly binds K + ions, was found to have a requirement of about 50 mM K + for the normal activity (Lindhauer & De Fekete, 1990), and surprisingly this is the minimal K + threshold that was recorded for all NaCl levels of the range (200–1000 mM) used here. The latter study also revealed that similar sized cations such as Rb + and Cs + being about 80% as effective as K + , while the replacement with Na + only brought about 20% of the overall enzyme activity.…”
Section: Discussionmentioning
confidence: 65%
“…Earlier Flowers and Dalmond (1992) have shown that protein synthesis in halophytes and glycophytes had different requirements for essential nutrients such as K and Mg, with the later impacting the polysome translocating system. Another evidence comes from the observation that starch synthetase, an enzyme that tightly binds K + ions, was found to have a requirement of about 50 mM K + for the normal activity (Lindhauer & De Fekete, 1990), and surprisingly this is the minimal K + threshold that was recorded for all NaCl levels of the range (200–1000 mM) used here. The latter study also revealed that similar sized cations such as Rb + and Cs + being about 80% as effective as K + , while the replacement with Na + only brought about 20% of the overall enzyme activity.…”
Section: Discussionmentioning
confidence: 65%
“…Within cells K is required for many physiological functions, including osmoregulation, enzyme activation and membrane transport processes (White and Karley 2010). Nitsos and Evans (1969) first observed that starch synthesizing enzymes have a specific requirement for K and about 1.8% of K (as a proportion of DM) is critical for high starch concentrations in potatoes (Forster and Beringer 1983;Lindhauer and De Fekete 1990). However, tuber K concentrations above 2% DM were found to reduce starch content (Marschner and Krauss 1980), which could be explained in terms of an osmotic optimum for starch synthesis (Oparka and Wright 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic P was positively correlated with the reducing sugar concentration in the stem portion of the tuber. Starch synthesizing enzymes have a specific requirement for K (24) and tubers depend upon a dynamic supply of K for highest starch content (19). About 1.8% K in the tuber dry matter is necessary for high starch concentrations but higher K concentrations tend to decrease starch concentrations (10).…”
Section: )mentioning
confidence: 99%